Immune responses in tuberculosis: antibodies and CD4-CD8 lymphocytes with vascular adhesion molecules and cytokines (chemokines) cause a rapid antigen-specific cell infiltration at sites of bacillus Calmette–Guérin reinfection - Shigenaga, T (Blackwell Science Inc, 2001)
Rabbit primary dermal bacillus Calmette–Guérin (BCG) lesions were compared with reinfection BCG lesions in order to gain insight into how immune responses protect against clinical tuberculosis. As early as 3 hr, a marked infiltration of macrophages and lymphocytes occurred in the reinfection group, while very little cell infiltration occurred in the primary group. It seems that only an antigen–antibody reaction could produce such an immediate pronounced antigen-specific chemotactic effect, because very few lymphocytes are normally present in the skin. Therefore, antibodies hasten the accumulation of an expanded antigen-specific T-lymphocyte population (memory cells) at sites of bacillary lodgement. By 1–2 days, the primary and reinfection BCG lesions differed 400- to 500-fold in size. By 4–5 days, the size of the reinfection lesions had declined, while the size of the primary lesions had increased, so that, grossly, both types of lesion were similar. At 8 days in reinfection lesions and at 12 days in primary lesions, small secondary peaks in size occurred, which were probably caused by cell-mediated immune responses. In rabbits with primary BCG lesions, skin tests with Old Tuberculin were positive at 9 days, accompanied by a rise in the levels of antibodies to the secreted antigen, phosphate-specific transport protein 1, but the levels of antibodies to the constitutive antigens, purified protein derivative and heat-shock protein 65, did not increase appreciably until some time after 23 days. In tissue sections of reinfection BCG lesions, the percentage of mononuclear cells labelled, by in situ hybridization techniques, for the mRNA of monocyte chemoattractant protein 1 (MCP-1), a chemokine, peaked at 3 hr and then was down-regulated, whereas in primary lesions, this percentage was down-regulated only after 2 days. [The percentage in the tissue sections for the mRNAs of interleukins 1β and 8, as well as the proteins of MCP-1 and tumor necrosis factor alpha (TNF-α), followed a somewhat similar time-course to that of MCP-1 mRNA.] A high percentage of mononuclear cells containing the MCP-1 mRNA ‘factory’ would favour enlargement of the lesions and a low percentage would favour their regression. At 5 days, the percentage of CD4 and CD8 lymphocytes, stained by immunohistochemical techniques, and the amount of microvasculature stained similarly for vascular cell adhesion molecule 1 were higher in the reinfection group, indicating that prior immunization caused a more rapid (antigen-dependent) up-regulation of these factors. Tuberculin reactions resembled early reinfection BCG lesions in almost every factor evaluated herein. In brief, the production of chemokines began soon after BCG reinfection, peaked within a few hours and was markedly down-regulated by 24 hr, a time at which the lesions of reinfection were of maximal size. Therefore, the amount of cell infiltration was tightly controlled, probably by the variety of mechanisms listed herein.